Martin Puchner, Poetry of the Revolution. Marx, Manifestos, and the Avant-Gardes 2006. - van den Berg, Hubert (Nordlit, 2007)
The genre of the manifesto belongs to the key elements of avant-garde textuality. As such, the manifesto has received considerable attention in recent avant-garde research. Many articles, chapters in general studies on the avant-garde, several collections of essays, monographs and annotated anthologies have been devoted to the manifesto in the past decades. Martin Puchner’s book on the avant-garde manifesto is a latecomer in this context, published some ten years after a wave of Manifestantismus struck in particular continental European avant-garde research. As in the case of any late arrival, the main question is self-evidently: what adds Puchner to already existing literature? The answer must be rather ambivalent. Puchner’s book definitely fills a lacuna in the Anglophone historiography of the avant-garde.